Combining EEG and Eye Tracking: Using Fixation-Locked Potentials in Visual Search - Brent Winslow; Angela Carpenter; Jesse Flint; Xuezhong Wang; David Tomasetti; Matthew Johnston; Kelly Hale (Bern Open Publishing, 2013)
Visual search is a complex task that involves many neural pathways to identify relevant areas of interest within a scene. Humans remain a critical component in visual search tasks, as they can effectively perceive anomalies within complex scenes. However, this task can be challenging, particularly under time pressure. In order to improve visual search training and performance, an objective, process-based measure is needed. Eye tracking technology can be used to drive real-time parsing of EEG recordings, providing an indication of the analysis process. In the current study, eye fixations were used to generate ERPs during a visual search task. Clear differences were observed following performance, suggesting that neurophysiological signatures could be developed to prevent errors in visual search tasks.